Husband's duty to maintain a working wife under Islamic and civil law in Malaysia: are the laws in harmony? - Mohd, Azizah; Hj Ibrahim, Badruddin; Abd Malek, Normi (Institut Sosial Malaysia & Faculty of Human Ecology, UPM, 2011)
Relationship between husband and wife creates certain rights and obligations that both of them are to enjoy and fulfill. Maintenance is one of the rights of the wife and one of the obligations of the husband. There is no dispute among the fuqaha as to the husband's duty to provide maintenance to his wife. This paper seeks to examine the provisions of Islamic law in Malaysia on husband's duty to maintain a working wife. The examination extends to the provision of Civil law in Malaysia, particularly the Married Woman and Children (Maintenance) Act (1950) and the Law Reform (Marriage and Divorce) Act 1976. Discussion will highlight the issue as to whether the two laws are in harmony when providing for such a duty to maintain on the husband. In addition, the paper will further highlight the husband's duty to maintain the wife in the situation where the wife is disobedient or nusyuz. The research reveals that the provisions of Islamic and Civil law in Malaysia on husband's duty to maintain a working wife, to a certain extent, are in harmony.